Changes in Lipid Peroxidation and Erythrocyte Resistance Indices Under Low Temperature Storage - Bogdanchikova, Oksana A.; Deineko, Anastasiia S.; ÐšÐ¾valenkÐ¾, A. A.; Ðžvsyannikova, Tetiana Ðœ.; Zabelina, I. A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 189.